MAKNA SIMBOL PROPERTI TARI JEPIN RAJUT SEMPURONG DALAM MASYARAKAT DESA SERIMBU KECAMATAN AIR BESAR - Yamas Yamas; Regaria Tindarika; Yudhistira Oscar Olendo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to describe the meaning of the symbol for the property ofthe Jepin Rajut Sempurong dance in the Serimbu Village community, AirBesar sub-district, Landak district. The property of Jepin Sempurongdance consists of three materials, that is rattan, cloth dan rope, the threematerials are formed into one unit. Rattan is interpreted as symbol of thecircle of brotherhood in the life of the serimbu village community, clothis interpreted as an intermediary or protector in a community life, ropeis interpreted as a binder in community life. So it can be concluded thatthe meaning of the symbol of the property of the jepin rajut sempurongdance in the serimbu village community is a circle of brotherhood insociety that must always be protected and tied so that it is not easilydivided.Keyword: Meaning Symbol, Property, Jepin Rajut Sempurong Dance